THE ROLE OF THE FAMILY PHYSICIAN IN THE EARLY DETECTION OF DIABETES MELLITUS - Abobakirova Odinaxon Olimjon qizi (TADQIQOTLAR, 2025)
ANNOTATION This  annotation  examines  the  critical  role  of  family  physicians  in  the  early detection  and  management  of  diabetes  mellitus.  Diabetes,  particularly  type  2,  has become  a  major  global  health  concern  due  to  its  increasing  prevalence,  long-term complications,  and  substantial  economic  burden.  Early  identification  of  diabetes  is essential  to  prevent  or  delay  complications  such  as  cardiovascular  disease, nephropathy, neuropathy, and retinopathy. Family physicians, as primary healthcare providers,  are  ideally  positioned  to  implement  screening  programs,  identify  at-risk individuals, and provide timely interventions.